RADT-33. LONG-TERM OUTCOMES, TREATMENT UTILIZATION, AND PROGNOSTIC FACTORS FOR PEDIATRIC CHORDOMA: AN NCDB ANALYSIS. (12th November 2021) - Cantrell, James; Acharya, Pawan; Vesely, Sara; Confer, Michael; Algan, Ozer; Gunter, Tyler
Abstract: BACKGROUND: Chordomas are rare tumors arising from the embryonal notochord presenting at the base of skull, spine, or sacrum. Pediatric chordomas (PC) comprise less than 5% of all chordomas and are more likely to be atypical or dedifferentiated. Evidence for management is limited to single institution series with 5-year overall survival (OS) between 60-100%. METHODS: Using the NCDB Participant User File, a retrospective observational cohort study was performed. The cohort was defined using the bone-soft-tissue, brain, and central nervous system databases selecting for cases with chordoma ICD-03 codes and age ≤ 25 years. Kaplan Meier method, log-rank test, and Cox proportional hazards regression were performed. RESULTS: 297 patients from 2004-2017 met inclusion criteria for descriptive analysis with 269 cases included for survival analysis. Mean age was 16.9 years, with 10% less than age 5. The cohort was 55% female, 8% Black, and 79% White. Primary sites included bones of the skull (70%), spine (22%), and pelvis (6%). Regarding treatment, 7% had no resection, 49% sub-total resection (STR), 33% gross-total resection (GTR), and 11% unspecified resection. 51% received radiation therapy with 46% of those receiving proton therapy. 7% received chemotherapy. The 1, 3, 5, and 10-year OS was 95%, 86%, 77%, and 72%. Selected prognostic factors from univariable OS model for OS analysis included: age > 5 (HR 0.30 (95% CI 0.16-0.57) p = 0.0002), surgical resection [GTR (HR 0.28 (95% CI 0.12-0.63) p = 0.0023) and STR (HR 0.27 (95% CI 0.12-0.59) p = 0.0011)], and radiation dose ≥ 7200cGy (HR 0.40 (95% CI 0.16-0.99) p = 0.047). CONCLUSION: In the largest cohort reported for PC, 3 and 10-year OS was 86% and 72%. Age, surgery, and radiation dose are important prognostic factors. Propensity score analysis to gauge effect of treatment, tumor, and patient characteristics on OS is forthcoming.